COLOR OF LIGHT-SOURCE AND BACKGROUND LUMINANCE ON PERCEIVED CONVEXITY AND CONCAVITY OF A BLURRED 3-D HEMISPHERE. - WEN-TE CHANG; LING-HUNG SOPHIA SHIH; KUO-CHEN HUANG (Perceptual & Motor Skills, 2012)
In the present study, the effect of light-source color, size, background luminance, and blur on the perceived convexity and concavity of a 3-D hemisphere was investigated. The sample consisted of 84 undergraduates divided into Experience and No-experience groups based on experience working with 3D software. Participants were asked to adjust the angle of light in a clockwise direction until a convex hemisphere appeared concave. Analysis indicated that the color of light had a statistically significant effect on the angle of adjusted light, and the Experience group adjusted the angle of light less than did the No-experience group. The angle of the adjusted light was significantly smaller under the high background luminance condition compared with the medium and low luminance conditions. The angle of adjusted light under the low blur condition was greater than that under the high and medium blur conditions. These results have implications for graphics-based interface design.